Single nucleotide variants in microRNA biosynthesis genes in Mexican individuals - Juárez-Luis, Jesús; Canseco-Ocaña, Moisés; Cid-Soto, Miguel Angel; Castro-Martínez, Xochitl H.; Martínez-Hernández, Angélica; Orozco, Lorena; Hernández-Zavala, Araceli; Córdova, Emilio J. (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) are important regulators in a variety of biological processes and their dysregulation have been associated with multiple human diseases. Single nucleotide variants in genes involved in the processing of microRNAs may alter miRNAs regulation and could present high allele heterogeneity in populations from different ethnic groups. Thus, the aim of this study was to genotyped 15 single nucleotide variants (SNVs) in 8 genes involved in miRNA processing pathway in Mexican individuals and to compared their frequencies across 21 populations from five continental groups. Method. Genomic DNA was extracted from 399 healthy Mexican individuals. SNVs in genes AGO2 (rs2293939, and rs4961280) DGCR8 (rs720012), DICER (rs3742330, and rs13078), DROSHA (rs10719, and rs6877842), GEMIN3 (rs197388, and rs197414), GEMIN4 (rs7813, rs2740349, and rs4968104), TNRC6B (rs9611280) and XP05 (rs11077, and rs34324334) were genotyped using TaqMan probes. Minor allele frequency of each SNV was compared using Chi2 test with those reported in the 1000 genomes database. Circles plots were performed with the circlize package to show the range of frequency of each variant and the number of countries that present the same frequency range. Result. All 15 SNVs were found in Hardy-Weinberg equilibrium in Mexican individuals, with prevalence ranging from 0.04 to 0.45. The SNVs rs4961280, rs2740349, rs34324334, and rs720012 in Mexican individuals showed one of the highest minor allele frequencies worldwide, whereas the minor allele frequencies of rs197388, rs10719, rs197414 and rs1107 was among the lowest in Mexican individuals. The variants showed high allele heterogeneity among the sub-continental populations, ranging from monomorphic, as was the case of rs9611280 and rs34324334 in African groups, to above 0.50, which was the case of variants rs11077 and rs10719 in most of the populations. Importantly, the variant rs197388, rs720012 and rs197414 showed FST values above 0.18, indicating directional selective process. Finally, the SNVs rs13078 and rs10719 showed significant correlation with both latitude and longitude. Conclusion. Our data suggest that worldwide distribution of the frequency of SNVs located in components of the miRNA processing pathway has been shaped by different adaptive forces, which could modify the genetic susceptibility associated with human diseases in populations with different ancestry.